Urban Informal Sector Workers during the Covid- 19 Pandemic in Indonesia: Social Networking as a Strategy for Business Sustainability - Sri Sunarti Purwaningsih; Haning Romdiati; Ade Latifa (UNHI PRESS, 2022)
Around 60,5% of workers in Indonesia rely on the informal sector, and in mid of 2020 almost half of them were in urban areas. The urban informal sector workers commonly are in small enterprises with low productivity, low liquidity, and negligible capital accumulation. They engage in street vending, home-based work, waste picking, domestic jobs, and other short-term contracts, and they do not enjoy workers’ benefis and social protection programs, thus they are vulnerable to shock, including Covid-19 pandemic. The pandemic does not only bring negative impact on the health sector, but it has also triggered an economic downturn. In terms of urban informal sector activities, various social policies (PSBB, Java-Bali PPKM, Emergency PPKM and Micro PPKM) sharply reduce the economic opportunities for informal economy workers who rely to a large extent on the personal contact with customers. Job losses and decreased income have been experienced by the majority of informal sector workers. This condition has to be overcome with various strategies to be able to maintain the continuity of their economic activities. This article discusses the strategies of urban informal sector workers to maintain sustainable livelihoods during the COVID-19 pandemic. The strategy carried out is focused on the use of social networks. The data used for writing this article is sourced from primary data. Data was collected using a qualitative approach in Bekasi Timur sub-district, Bekasi City, West Java Province. In addition, the article also uses the existing data related to the issued being studied.